Beclabuvir for the treatment of hepatitis C. (August 2015) - Gentile, Ivan; Zappulo, Emanuela; Buonomo, Antonio Riccardo; Maraolo, Alberto Enrico; Borgia, Guglielmo
<x xml:space="preserve">Abstract</x> Introduction: About 185, 000, 000 people worldwide are chronically infected with hepatitis C virus (HCV). Currently, the most successful HCV infection antiviral therapies reduce the chance of progression towards the advanced phases of the hepatopathy (liver cirrhosis, hepatocellular carcinoma and death). Recently, however, several new direct-acting antivirals against HCV are available or are in an advanced phase of clinical development. Areas covered: This review focuses on <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=beclabuvir&logicalOpe1=OR&field2=articletitle&text2=beclabuvir&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">beclabuvir, an allosteric non-nucleotide inhibitor of HCV polymerase. The article covers its pharmacokinetics, mechanism of action, in addition to its tolerability and safety profile as well as its resistance pattern. Expert opinion: The pharmacokinetic, efficacy and tolerability profile of beclabuvir, as well as its barrier to resistance, are very favorable. In particular, the combination of beclabuvir with asunaprevir and daclatasvir achieves very high rates of viral eradication (about 90%) in patients infected with HCV genotype 1, which is the most common genotype worldwide. Therefore, beclabuvir represents a powerful weapon against HCV infection and has to be considered an optimal option in tailored IFN-free combinations.